Геолого-геохимические особенности алевролитов майкопа Керченского полуострова - Скорик, А.Н.; Байраков, В.В. (Видавничий дім "Академперіодика" НАН України, 2007)
Mineralogical, petrographical, and geochemical peculiarities of the Kerch peninsula Maikop aleurolites teslify the fact that they had been formed as a result of a washout of the kaolin crust of weathering of Near-Azov shield acid rocks and a delivery of a terrigenous material during the disintegration of Jurassic conglomerates and Cretaceous sandstones of the Upland Crimea.